Laser-Ironing Induced Capping Layer on Co-ZIF-L Promoting In Situ Surface Modification to High-Spin Oxide–Carbon Hybrids on the “Real Catalyst” for High OER Activity and Stability - Weihao Liu (2024)
10.1002/adma.202310106